Fiscal and External Sustainability: A Two-Step Time-Varying Granger Causality Assessment - António Afonso; José Alves; José Carlos Coelho; Jamel Saadaoui (CESifo GmbH, 2025)
We implement a two-step analysis of fiscal and external causality patterns using a data set covering the 27 EU countries in the period 2002Q1-2023Q4. In the 1st step, we compute fiscal and external sustainability time-varying coefficients, modelling the cointegration relationship between government revenues and government spending, and between exports and imports. In the 2nd step, we use three recursive strategies, combined with Granger causality tests: forward expanding, rolling, and recursive window methods to capture causal relationships. Our results show that: (i) peripheral countries have lower sustainability coefficients, while non-Eurozone countries have higher sustainability coefficients, (ii) after the 2008 global financial crisis, there was an improvement in fiscal and external sustainability for most countries, (iii) during the Eurozone crisis in 2010-2012, in Austria, France, Greece, Ireland, Netherlands, Slovakia and Spain, there was causality between fiscal and external sustainability, (iv) during that period, causality was observed between the external and fiscal sustainability in EMU countries (Austria, Germany, Malta, Netherlands, Slovakia, Slovenia, Spain) and in non-EMU countries.
Keywords: C22; C23; F32; F41; H30; H62; 330; fiscal sustainability; external sustainability; European Union; time-varying causality; lag-augmented vector autoregression